Pengaruh Model Pembelajaran Tuntas (Mastery Learning) terhadap Minat dan Ketuntasan Belajar Siswa Kelas VIII MTs - Ratnasari, Sri Ayu (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2023)
This research is motivated by the low quality of education, such as the low interest of students in Biology, the low mastery of students in Biology, and monotonous learning. The purpose of this research is to increase students' interest and mastery learning through Biology learning based on mastery learning for class VIII MTs students. Darussalam Bermi, Gerung District, West Lombok Regency. The type of research used in this research is quasi-experimental (quasi-experimental). The population in this study were all students of class VIII MTs. Darussalam Bermi, totaling 112 people, while the sample in this study was class VIII B as an experimental class with 27 students and class VIII C as a control class with 29 students. The research design used in this research is Nonequivalent control group design. The data collection used in this study was in the form of a test technique, namely in the form of a pre-test and post-test to determine the initial ability and final ability of each student as well as a questionnaire technique to determine students' learning interest in Biology. The results of the study were pre-test and post-test data with an average value of 50.34 for the control class, increasing to 61.72 and for the experimental class, with an average value of 53.33, increasing to 77.41. As well as the results of the research in the form of data from a questionnaire on student interest in learning with the percentage of student interest in the control class reaching 81.18% with a very high interest category, and in the experimental class the percentage of student interest in learning reached 82.15% which is also included in the very high interest category. Based on the calculation results, it was found that tcount = 5.25 and ttable = 1.684. If t count > t table then the H0 hypothesis is rejected and Ha is accepted. This means that there is an influence of mastery learning model on student learning completeness.